Laterally positioned flap with chorion membrane for coverage of isolated gingival miller class III recession - Deepak Sharma (Indian Journal of Dental Sciences, 2019)
The treatment of gingival recession (GR) defects is indicated for esthetic reasons, to reduce root sensitivity, to remove muscle pull, and to create or augment keratinized tissue. Various root coverage procedures have been used to cover localized GRs, such as laterally repositioned flaps (LPF), coronally advanced flaps, free gingival grafts, connective tissue pedicle flaps with a free gingival graft, subepithelial connective tissue grafts, acellular dermal matrix allografts, and guided tissue regeneration. The predictability of these perioplastic surgery procedures may be associated with different conditions, especially the initial recession classification. This report discusses Miller Class III isolated GR case with interproximal bone loss and wide and deep defects treated with a combination procedure of an LPF and chorion membrane.